Caribbean Report 23-06-1995 - Crosskill, Hugh (anchor); Ninvalle, Pete (correspondent); Cadasse, Noel (interviewee); Flemming, Charles (interviewee); Hudson-Phillips, Karl (interviewee); Ford, Henry (interviewee); Kinzer, Joseph (interviewee); Bhola, Ronnie (correspondent); Mann, Simon (correspondent); Jagan, Cheddi (interviewee); Doueb, Rafael (interviewee); Ransome, Debbie (correspondent); et al. (The British Broadcasting Corporation, 1995)
In this report: the strike by public sector workers in St. Lucia continues and President of the St. Lucia Hotel and Tourism Association, Mr. Noel Cadasse expresses concern that this protracted strike could have catastrophic consequences for the tourism industry. As the commission of inquiry into the UN funds scandal continues in St. Lucia, Dr. Charles Flemming received a thorough cross examination from both counsels Karl Hudson-Phillips and Henry Ford. In Haiti, the integrity of the electoral process is questioned ahead of legislative and local elections. Guyana's President Cheddi Jagan states any member of his government that fails to maintain high moral and ethical standards would have to go and announced plans to introduce an Integrity Commission in the near future. In cricket, England fights back on the second day of the second test match against the West Indies. Vice-President of France Libertes Rafael Doueb argues that the human rights situation in Cuba may not be as bad as feared and that there are other countries in the hemisphere with much worse records. Jose Miguel Vivanco, Human Rights Watch Americas was less positive about the situation in Cuba.
1. Headlines with Hugh Crosskill (00:00-00:29)
2. St. Lucia's prolonged public sector strike could have catastrophic consequences for its tourism industry (00:30-02:52)
3. Dr. Charles Flemming received an intense grilling as the commission of inquiry into the UN funds scandal continued in St. Lucia (02:53-04:59)
4. There are fears of fraud in the run-up to elections in Haiti (05:00-07:36)
Keywords: Tourism -- Economic aspects -- Saint Lucia; Strikes and lockouts -- Civil service -- Saint Lucia; Industrial relations -- Saint Lucia; Governmental investigations -- Saint Lucia; Political corruption -- Saint Lucia; Saint Lucia -- Politics and government; Elections -- Haiti; Elections -- Corrupt practices -- Haiti; Haiti -- Politics and government -- 1986-; Democracy -- Haiti; Guyana -- Politics and government; Political ethics -- Guyana; Public administration -- Moral and ethical aspects -- Guyana; Integrity; Cricket -- West Indies; Cricket -- Tournaments -- England; Human rights -- Cuba; Civil rights -- Cuba; Cuba -- Social conditions